Pengaruh Metode Team Games Tournament terhadap Hasil Belajar Siswa pada Pelajaran PAI di SDN 22 Andalas - Ramadani, Putri; Wirdati, Wirdati (Lembaga Yasin AlSys, 2025)
The teaching method used by teachers at SDN 22 Andalas Barat is still predominantly lecture-based, resulting in a passive and monotonous classroom atmosphere, which negatively impacts student learning outcomes. This study aims to examine the effect of the Team Games Tournament (TGT) method on improving the learning outcomes of fifth-grade students (Phase C) in the Islamic Education subject. The research employed a quantitative approach with a quasi-experimental design, involving 44 students selected from a total population of 67 through purposive sampling. Data were analyzed using SPSS 26, applying the paired sample t-test, independent sample t-test, and N-Gain score calculation. The paired sample t-test showed a t-value of 14.192 with a significance level of 0.000 (p < 0.05), and the independent sample t-test yielded a t-value of 2.188, which is greater than the t-table value of 2.01808, with a significance level of 0.044, indicating a significant effect of the TGT method on student learning outcomes. The average N-Gain score of 0.523 indicates a moderate level of improvement. In conclusion, the Team Games Tournament method is proven to be more effective than the lecture method in enhancing student learning outcomes. The implications of these findings highlight the importance of implementing active and collaborative learning methods to create a participatory classroom environment that supports improved academic achievement.